Contribución al conocimiento de los foraminíferos del Rocanense de la cuenca de Añelo (provincia de Neuquén) - Mailhe, A. R. (1967)
A foramíníferal fauna From three profiles coIlected in cuenca de Añelo (Provincia de Neuquén ) has been studíed. A list of bentonic and planctonic specimens ís given. From planctonic foramínífera Globoconusa daubiergensis, Subbotina triloculidinoides and Turborotalia peudobulloides, a Lower Paleocene age js assigned to the studied samples.